Computational regionalism: De-familiarization of tectonics in the wire-bending craft. (June 2022) - Noel, Vernelle AA
Computer-based design and fabrication systems in architecture contain modes of operation and preferences that often constrain tectonic possibilities in design and construction. These predispositions neglect architecture's cultural and material dimensions, resulting in universalizing tectonics that erase nuances of place, culture, and expression in design. How may we celebrate local tectonic languages while also revisiting them through computer-based systems in architecture? The project examined here highlights novel possibilities for cultural expression and craftsmanship through computational design methods, retaining the expressive potential of a local craft while de-familiarizing its cultural context. I analyze how shape grammars and digital fabrication methods deployed in design, de-familiarizes the craft of wire-bending in costuming in the Trinidad Carnival. I present and apply new rules for the craft's computational description based on material tests and an architectural application to expand discourses on critical regionalism. I adopt Tabbarah's term "computational regionalism" to describe this process and elaborate it as a five-step sequence. Computational regionalism employs computational methods to translate local craft knowledge and tectonic languages into new interpretations and poetics of construction. Its process of creative de-familiarization raises critical questions about the local and the universal.